Disability status, individual variable pay, and pay satisfaction: Does relational and institutional trust make a difference?. Issue 1 (4th September 2017) - Shantz, Amanda; Wang, Jing; Malik, Amina
Abstract : Although prior research suggests that disabled employees have different needs in the context of some HRM practices, we know little about their reactions to reward systems. We address this gap in the literature by testing a model using the 2011 British Workplace Employee Relations Survey (disabled employees, n = 1, 251; nondisabled employees, n = 9, 959; workplaces, n = 1, 806) and find that disabled employees report lower levels of pay satisfaction than nondisabled employees, and when compensated based on individual performance, the difference in pay satisfaction is larger. We suggest that relational (derived from trust in management) and institutional (derived from firm‐wide policies and HRM practices, both intended to provide equitable treatment to disabled employees) forms of trust play important roles. The results of multilevel analyses show that when trust in management is high, the difference in pay satisfaction under variable pay is reduced. We find just the opposite for employees who work in organizations with a formal disability policy but without supportive HRM practices; the gap in pay satisfaction is exacerbated. However, the combination of the presence of a firm‐wide policy and HRM practices reduced the difference in pay satisfaction. Implications of the findings for theory, future research, and management practice are discussed.